The Influence of Financial Technology and Sharia Compliance on Consumer Trust (A Study on Students of the Faculty of Economics and Business, Mulawarman University, Users of Quick Response Code Indonesian Standard Mobile Banking by Bank Syariah Indonesia) - Putri, Noor Armalia; Purwanti, Purwanti; Fitriah, Rinna Ramadhan Ain; Adawiyah, Rabiatul (Borneo Islamic Finance and Economics Journal, 2025)
This research was conducted by Noor Armalia Putri with the title "The Influence of Financial Technology Innovation and Halal Aspects on Consumer Trust (Study on Students of the Faculty of Economics and Business, Mulawarman University, Users of Quick Response Code Indonesian Standard Mobile Banking by Bank Syariah Indonesia)" under the guidance of Purwanti. This research aims to determine the influence of financial technology innovation and halal aspects on consumer trust among students at the Faculty of Economics and Business, Mulawarman University who use QRIS Mobile Banking by Bank Syariah Indonesia. The method used in this research is a quantitative approach. The population in this study was active students of the Faculty of Economics and Business, Mulawarman University, with a total sample of 97 respondents selected through purposive sampling. Data collection was carried out through questionnaires distributed via Google Forms on the WhatsApp application. Data analysis techniques included validity tests, reliability tests, ordinal logistic regression analysis, overall model fit tests, goodness of fit tests, Nagelkerke R Square, and Wald tests (partial t-tests). The results of this research indicate that both financial technology innovation and halal aspects have a positive and significant influence on consumer trust. This shows that students who benefit from technological convenience and believe in the halal integrity of the system tend to have higher trust in QRIS services by Bank Syariah Indonesia.. Keywords: Financial Technology Innovation, Halal Aspects, Consumer Trust